ANALYSIS OF MATHEMATICAL LITERACY ABILITY OF SMPN 3 TARAKAN STUDENTS IN SOLVING HIGHER ORDER THINKING SKILLS (HOTS) QUESTIONS IN TERMS OF LOW LEARNING ACHIEVEMENT - Setia Widia Rahayu; Fendi Nurdianto (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
This research is a qualitative descriptive study that aims to describe the mathematical literacy ability of class VII students of SMPN 3 Tarakan in solving HOTS questions. Based on the results of the study, the mathematical literacy ability of class VIII students in solving hots questions was at level 2, namely: Developing and identifying problems, and setting assumptions. Select, compare, and evaluate appropriately problem solving strategies related to complex problems related to the model. Uses broad thinking and reasoning, and correctly relates representations. Reflect on their work and be able to formulate and communicate their interpretations and reasons.Keywords: Mathematical Literacy, Higer Order Thinking Skills, Low Learning Achievement